REGISTRATION-BASED WELL-KNOWN MARKS: INDONESIAN PRACTICE AND NORM UNDER PARIS CONVENTION AND TRIPS - Alam Wibowo, Richard Jatimulya; Priyono, Joko (Fakultas Hukum Universitas Islam Indonesia, 2026)
The recognition of well-known marks by Indonesian courts has a long history in both legislation and jurisprudence. Current practice indicates that such recognition is often based on the registration of the mark in several countries. Although this approach is permissible under Indonesian law, it is not explicitly provided for in the Paris Convention or TRIPS which serve as international standards for the protection of well-known marks. Hence, this doctrinal or normative legal research will analyze the practices of recognizing well-known marks based on registrations in several countries within the legal framework of Indonesia, the Paris Convention, and the TRIPS Agreement. The findings reveal that early developments in Indonesian marks law and judicial precedents have greatly influenced the practices of recognizing well-known marks based on registrations in several countries. However, these practices are found to be inconsistent with the provisions concerning well-known marks under the Paris Convention and TRIPS. Therefore, Indonesian courts are encouraged to give greater consideration to Paris Convention and TRIPS to develop recognition practices that align more closely with international standards.